A PART OF THE STARRY SKY DESCRITION FORMIG WHEN TV OBSERVATION - Sukhov, P. P.; Strygin, N. Z. (Одеські астрономічні публікації, 2017)
The observing part of the starring sky is represented by two-dimentional pulse parametric field M, M = [(S,B,(X0,Y0)i], i = 1,n. Where(X0,Y0) - optical radiation centroid's coordinates, B - Summary radiation (brightness), S - the object's area Compact object's isolation and their parameters S, B, (X0, Y0) determination real time algoritm is developed. The method may be realised by a middle class computer vision system (CVS). The CVS computing system may be realised by convejor inhomogeneous structure "base computer + functional oriented processor" (BC + FOP). Some FOp's units are developed. The method's efficiency was carried out when imitation testing of binary image models.